Reporting the climate change crisis - Carvalho, Anabela (2010)
Climate change is one of the most serious threats that humankind will have to deal with in the coming decades. There is every indication that it will engender a significant upheaval in the climate patterns of the world regions, with corresponding impacts on agriculture, ecosystems and human health. This main entail unpredictable weather events, like storms and tornados, while posing significant risks for human security, destruction of housing and economic structures, and flooding of low lying countries, among other effects (IPCC 2007). The enhanced greenhouse effect is a complex, multi-dimensional issue, both in terms of causes and effects. The production of greenhouse gases (GHGs), which strongly influence the Earth’s climate, is deeply embedded in the way in which modern societies work: in transportation, heating, the production of goods, and so forth. Climate change has strong links with powerful economic activities and organizations, such as the oil industry. Therefore, tackling the problem requires an unprecedented level of coordination between governments, industry and consumers in a short time-scale. The precise definition of the problem is itself a battlefield, where different actors - NGOs, corporations, scientific community, etc. - attempt to make their views prevail. This conceptual struggle will have material consequences, since the solutions are conditioned by what is understood to be the problem. The news media, as a key space for the production, reproduction and transformation of meanings, play an important role in this process, influencing both social representations and policy-making on this issue (e.g. Cabecinhas, Lázaro and Carvalho in press; Corbet and Durfee 2004; Wilson 1995). This chapter focuses on the roles that the mainstream media have played in the last two decades in the social construction of climate change and in the relations between science, policy and public opinion. By mainstream media I mean the major television networks, newspapers and magazines with high circulation, and radio channels with significant audiencesi. Alternative media, such as community media, blogs, social movements’ online news and other citizen-produced content on the internet, continue to grow in importance; however, the fragmented nature of the audiences of these media complicates the evaluation of their social impact and turns them into more difficult research objects than the traditional media. The chapter will discuss the challenges that climate change poses to the media, the dominant public and political discourses, and some of the emerging issues and questions to be addressed by researchers.